2007
DOI: 10.1037/0893-3200.21.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep timing and quantity in ecological and family context: A nationally representative time-diary study.

Abstract: Associations between demographic characteristics, school schedules, activity choices, family functioning, and sleep behaviors were estimated using nationally representative time-diary data from 2,454 children (ages 5.5 to 11.9 years) and adolescents (ages 12.0 to 19.1 years). For weekdays, African American adolescents, Asian children, and those with earlier school start times and longer travel times to school reported fewer sleep hours. More time spent watching television (for children), doing homework (for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
305
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(335 citation statements)
references
References 74 publications
(87 reference statements)
26
305
4
Order By: Relevance
“…25,26 Our findings are consistent with reports from cross-sectional studies [8][9][10][11][12] and a couple of longitudinal 16,17 and experimental studies 27,28 which suggested that disruptions to sleep are linked to behavioral difficulties in children. In keeping with previous studies, 26,[29][30][31] other markers of the family milieu that we know are important predictors of early child development, 2 including mother' s mental health and daily routines (eg, skipping breakfast, reading to or with child, having a TV in the bedroom, and the amount of TV watched), were all strongly correlated with not having a regular bedtime. We found that statistical adjustment for these factors attenuated associations, so our results suggest that having a regular bedtime is important alongside other aspects of family routines.…”
Section: Figuresupporting
confidence: 82%
“…25,26 Our findings are consistent with reports from cross-sectional studies [8][9][10][11][12] and a couple of longitudinal 16,17 and experimental studies 27,28 which suggested that disruptions to sleep are linked to behavioral difficulties in children. In keeping with previous studies, 26,[29][30][31] other markers of the family milieu that we know are important predictors of early child development, 2 including mother' s mental health and daily routines (eg, skipping breakfast, reading to or with child, having a TV in the bedroom, and the amount of TV watched), were all strongly correlated with not having a regular bedtime. We found that statistical adjustment for these factors attenuated associations, so our results suggest that having a regular bedtime is important alongside other aspects of family routines.…”
Section: Figuresupporting
confidence: 82%
“…Adolescents with parent-set bedtimes of 10:00 p.m. or earlier are 24 % less likely to experience depression and 20 % less likely to have suicidal ideation in comparison to adolescents with parent-set bedtimes of midnight or later (Gangwisch et al 2010). Likewise, in a representative time-diary study of over 2,400 youth in the US, stricter household rules were associated with adolescents obtaining more weekday sleep hours (and an early bedtime); this association was specific to adolescents and not found among children (Adam et al 2007). Conversely, although not associated with overall sleep duration, parenting styles characterized by restriction, reproach, and inconsistency are associated with adolescents experiencing poorer sleep quality and greater daytime sleepiness (Brand et al 2009).…”
Section: Family Factorsmentioning
confidence: 95%
“…For example, a series of studies conducted with adolescents in São Paulo, Brazil showed employment to be a significant predictor of shorter sleep duration, poorer sleep quality, greater daytime sleepiness, and a greater sleep rebound (i.e., extended sleep duration) on weekends (Fischer et al 2008;Teixeira et al 2004a, b;2007). In a study conducted by a different research team, weekend employment was linked to less total sleep time (due to earlier wake times), with each hour of paid work corresponding to a quarter-hour reduction in weekend sleep obtained (Adam et al 2007). College students who work 20 h or more each week also obtain less sleep than their peers working less than 20 h per week , demonstrating the association between employment and reduced sleep to extend into late adolescence.…”
Section: Homework Employment and Extracurricular Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Indeed, in-room access to a TV, computer, or electronic games has been shown to be associated with less total sleep in previous studies. [17][18][19][20] Similarly, children who spend more time using these media sleep less, 17,[21][22][23] leading some researchers to speculate that bedroom access to screen-based media may have an indirect effect on sleep. 16 However, to the best of our knowledge, no study has specifically tested this indirect effect hypothesis, nor has any study examined how media use relates to sleep among individuals with ASD or ADHD.…”
mentioning
confidence: 99%